Diabetes Screening and Prevention in a High-Risk, Medically Isolated Border Community - Millard, Ann V.; Graham, Margaret A.; Mier, Nelda; Moralez, Jesus; Perez-Patron, Maria; Wickwire, Brian; May, Marlynn L.; Ory, Marcia G. (Frontiers in Public Health, 2017)
Introduction: An innovative project, POWER vs. Diabetes (Prevention Organized against Diabetes and Dialysis with Education and Resources), offered diabetes prevention information, screening, and medical referrals in a community setting at the Texas-Mexico border. The site was a large, longstanding, indoor-outdoor flea market similar to a shopping mall for low-income people. The priority population included low-income Hispanic urban and rural people with tenuous access to medical services. The program addressed those with diabetes and prediabetes, and accompanying relatives. Background: People living in the Lower Rio Grande Valley (LRGV) face challenges of high rates of type 2 diabetes, lack of knowledge on prevention, and inadequate access to medical care. Recent statistics from actual community-wide screenings indicate that an especially high prevalence of diabetes with reported rates of 30.7% among adults in the LRGV compared with nationwide estimates of 12.3%. Methods: A diverse team composed of public health faculty, students, a physician, a community health worker, and community volunteers conceived and developed the project with a focus on cultural and economic congruence and a user-friendly atmosphere. The program provided screening for prediabetes and diabetes with a hemoglobin A1c test. Screening was offered to those who were at least 25 years of age and not pregnant. When results indicated diabetes, a test for kidney damage was offered (urinary albumin-to-creatinine ratio (ACR)). Diabetes referrals within the week were provided with a medical appointment at a community clinic for those without a medical home. Health education modules addressed all family members. Discussion: The project was successful in recruiting 2,332 high-risk people during 14 months in a community setting, providing clinic referrals to those without medical care, introducing them to treatment, and providing diabetes prevention information to all project participants. Implications for research and practice are highlighted. Conclusion: This study shows that a regular access point in a place frequented by large numbers of medically marginalized people in a program designed to eliminate cultural and economic barriers can succeed in providing a hard-to-reach community with diabetes prevention services. Aspects of this program can serve as a model for other service provision for similar populations and settings.